TOMATO BENEFITS IN REDUCING THE RISK OF PROSTAT CANCER - Mataram, Kadek Wisnu; Ika Wahyuniari, Ida Ayu (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Consumption of fresh and processed tomato products is associated with reduced risk of prostate cancer . The emerg in g hypothesis is that lycopene, the primary red carotenoid in tomatoes , may be the pr in ciple phytochemical responsible for this reduction in risk. A number of potential mechanisms by which lycopene may act have emerged, in clud in g serv in g as an important in vivo antioxidant, enhanc in g cell-to-cell communication via in creas in g gap junctions between cells, and modulat in g cell-cycle progression. Although the effect of lycopene is biologically relevant, the tomato is also an excellent source of nutrients, in clud in g folate, vitam in C, and various other carotenoids and phytochemicals, such as polyphenols, which also may be associated with lower cancer risk. Tomatoes also conta in significant quantities of potassium, as well as some vitam in A and vitam in E. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: tomato, lycopene, prostate cancer